Young Women’s Knowledge of the Risks of Teenage Pregnancy - Adriana Bangun; Sabarina Tarigan; Kiki Khoiriyani; Putri Diah Pemiliana (International Journal Of Health Science, 2025)
Teenage pregnancy is a pregnancy that occurs in women aged 11-19 years. Knowledge by teenagers greatly influences the attitudes or behavior of teenagers, both positive and negative, towards teenage pregnancy. This study aims to determine the description of teenage girls’ knowledge about the risks of pregnancy in adolescence. This study uses a descriptive research design with a survey approach, with a population of 103 female students and a total sampling sample of 103 respondents. This study uses a questionnaire as a research instrument and data are analyzed using frequency distribution. The results of this study indicate that 81 respondents (78.6%) of teenage girls at Primbana Private High School have a sufficient level of knowledge, 15 respondents (14.6%) have a low level of knowledge, and 7 respondents (6.8%) have a good level of knowledge. The conclusion is that most teenage girls at Primbana Private High School have a sufficient level of knowledge about the risks of teenage pregnancy and a small number have a good level of knowledge about teenage pregnancy.